2014
DOI: 10.1158/1078-0432.ccr-13-0582
|View full text |Cite
|
Sign up to set email alerts
|

The Disparate Twins: A Comparative Study of CXCR4 and CXCR7 in SDF-1α–Induced Gene Expression, Invasion and Chemosensitivity of Colon Cancer

Abstract: Purpose: In colorectal cancer, increased expression of the CXC chemokine receptor 4 (CXCR4) has been shown to provoke metastatic disease due to the interaction with its ligand stromal cell-derived factor-1 (SDF-1). Recently, a second SDF-1 receptor, CXCR7, was found to enhance tumor growth in solid tumors. Albeit signaling cascades via SDF-1/CXCR4 have been intensively studied, the significance of the SDF-1/CXCR7-induced intracellular communication triggering malignancy is still only marginally understood.Expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 49 publications
(66 reference statements)
3
50
0
Order By: Relevance
“…An elevated level of another SDF-1 receptor, CXCR7, has been reported in CRC brain metastasis as well as in certain classes of aggressive colon tumor. [24] Thus, the expression of CXCR7 in our study could reflect the metastatic status of the CRC patient.…”
Section: Discussionmentioning
confidence: 68%
“…An elevated level of another SDF-1 receptor, CXCR7, has been reported in CRC brain metastasis as well as in certain classes of aggressive colon tumor. [24] Thus, the expression of CXCR7 in our study could reflect the metastatic status of the CRC patient.…”
Section: Discussionmentioning
confidence: 68%
“…This study was initiated from the aspect of CXCR7 expression, and its correlation with tumor grade, tumor stage, and lymph node metastasis. In cervical cancer research [30], colorectal cancer research by Xu et al [19] cutaneous squamous cell carcinoma research by Hu et al [21] renal cancer research by Wang et al [26] and gallbladder cancer research by Yao et al [27] all of these studies have consistent results for tumor grade, stage and lymph node metastasis [30][31][32][33][34]. These significant clinicopathological relative factors revealed their roles in tumor development [35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 97%
“…CXCR7 expression, which was mediated by TLR4, promoted tumor cell proliferation and migration in human colorectal carcinoma (38). In addition, higher rates of CXCR7 expression were confirmed in colorectal carcinoma tissues compared with those in normal tissues, and the high CXCR7 expression was associated with aggressive tumor behavior, including large tumor size, high TNM stage, high histological grade, and lymph node metastasis (38,42). Guillemot et al (39) also demonstrated that CXCR7 and its ligands were overexpressed in human colorectal cancer and that CXCR7 facilitated the progression of colon cancer in the lungs of a pulmonary metastasis mouse model.…”
Section: Colorectal Cancermentioning
confidence: 98%
“…Previous studies have demonstrated that CXCR7 is differentially expressed in colorectal cancer at the transcriptional and protein levels, as well as in the cell membrane (38)(39)(40)(41)(42)(43). CXCR7 expression increased following lipopolysaccharide treatment in the SW480 and COLO 205 colorectal carcinoma cell lines, which express Toll-like receptor 4 (TLR4)/myeloid differential protein-2.…”
Section: Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation